ASSESSMENT AND CONTROL OF QUALITY OF EDUCATION OF STUDENTS IN KONSTANTIN PRESLAVSKY UNIVERSITY OF SHUMEN: ASSESSMENT AND CONTROL OF QUALITY OF EDUCATION OF STUDENTS IN KONSTANTIN PRESLAVSKY UNIVERSITY OF SHUMEN - GEORGIEVA, BOGDANA; NIKOLOVA, SNEZHANA (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The period from 2009 to 2011 can be described with a quality of new moments, requirements and more and more complex criteria relating to the educational process and the whole education of students. Bulgaria, as a member of the European Union, holds up to the normative and strategic documents. The University of Shumen attends and necessitates the comprehension to execute these, who premise the development of higher education – the European Qualifications Framework and her endorsement into the “The National Qualifications Framework”(2011), “Manual of appliance of the credential system”(2009), “Europe 2020”(2010). The following article examines the quality education of students in the University of Shumen.